2022
DOI: 10.1111/jocs.16668
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic time and patient outcomes after the 2018 UNOS donor heart allocation system change

Abstract: Background The allocation system for heart donors in the United States changed on October 18, 2018. The typical distance from donor hospitals to recipient hospitals has increased as has the ischemic time. We investigated patient outcomes with the new allocation system and the differential effects of ischemic time under both the old and new allocation schemas. Methods The United Network for Organ Sharing Registry (UNOS) was queried for data regarding heart transplants occurring from October 1, 1987 to March 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…One UNOS registry study extending from 1 October 1987 through 1 March 2021, included a total of 62 301 adult heart transplants and investigated survival outcomes at 30 days and 1 year with the new allocation system. After adjusting for ischemic time, survival outcomes remained unchanged at both 30 days and 1 year [13 ▪▪ ]. This analysis also highlighted a longer ischemic time in the new allocation system (mean 3.43 vs. 3.03 h, P < 0.001), which remains an influential factor in recipient survival (Fig.…”
Section: Impact Of the Allocation Changes On Posttransplant Survivalmentioning
confidence: 64%
“…One UNOS registry study extending from 1 October 1987 through 1 March 2021, included a total of 62 301 adult heart transplants and investigated survival outcomes at 30 days and 1 year with the new allocation system. After adjusting for ischemic time, survival outcomes remained unchanged at both 30 days and 1 year [13 ▪▪ ]. This analysis also highlighted a longer ischemic time in the new allocation system (mean 3.43 vs. 3.03 h, P < 0.001), which remains an influential factor in recipient survival (Fig.…”
Section: Impact Of the Allocation Changes On Posttransplant Survivalmentioning
confidence: 64%
“…Organ transport distance differences between donors in facilities versus hospitals observed in this study were not directly comparable to higher local rates transplantation rates reported in the first few years of operation of one OPO-based facility opening, 11 but were consistent with shorter distances traveled for kidneys and livers recovered in facilities. 11 Because more cohort donors underwent recoveries in facilities over time, 10 observed differences may reflect changes in specific organ allocation rules during the study period 19 or greater willingness of distant transplant programs to travel to OPO-based facilities located near major airports (requiring less travel time than to reach more remote donor hospitals within the same OPO region). 24 It is not yet known whether organ recovery facilities may mitigate or exacerbate known geographic disparities in access to transplantation within or across donor service areas and UNOS regions.…”
Section: Discussionmentioning
confidence: 99%
“…As organ ischemic time has been associated with transplantation outcomes, 16,[18][19][20] the primary outcome of interest was an organ-specific ischemic time (from the application of aortic cross-clamp to reperfusion in the recipient) for each type of organ transplanted with data captured in the study dataset (total ischemic times for hearts and lungs, and cold ischemic times for kidneys and livers, ischemic times hereafter). Times measured from multivisceral transplants (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A pig heart was recently transplanted into a human recipient 6 . But as the work of Siddiqi and colleagues suggests, perhaps the most significant disruptions to the management of advanced heart failure occurred with the United Network for Organ Sharing (UNOS) policy changes on October 18, 2018 7 …”
Section: Figurementioning
confidence: 99%
“…6 But as the work of Siddiqi and colleagues suggests, perhaps the most significant disruptions to the management of advanced heart failure occurred with the United Network for Organ Sharing (UNOS) policy changes on October 18, 2018. 7 The full impact of the new system will likely take several more years to materialize, but a number of trends are already apparent (and supported by this important contribution to the Journal of Cardiac Surgery). 8,9 Instituting short term MCS in the form or extracorporeal membrane oxygenation, percutaneous ventricular assist device, or intraaortic balloon pump support offers patients the opportunity for shorter waiting times and access to higher quality organs.…”
mentioning
confidence: 98%